Lightweight aggregate based on phosphogypsum and multi-source solid waste as well as preparation and utilization methods thereof

By using alkali activaters and premature strength agents in the preparation method of light aggregates for phosphogypsum and multi-source solid waste, gel polymer materials are formed, and the utilization rate of phosphogypsum and multi-source solid waste is solved. The energy-energy of phosphogypsum and multi-source solid waste is solved. The problems of large consumption and insufficient water stability have achieved efficient and environmentally friendly reuse and improved material performance.

CN119504188APending Publication Date: 2025-02-25CHANGAN UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411654474.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the utilization rate of phosphogypsum and multi-source solid waste is low, the energy consumption is large, and the carbon emissions are high, and the reuse products of phosphogypsum are insufficient in the long-term water stability.

Method used

Using light aggregate preparation method based on phosphogypsum and multi-source solid waste, the phosphogypsum and multi-source solid waste are gelled through alkali exciters, thereby forming a gel polymer material, avoiding the use of cement, reducing energy consumption and Carbon dioxide emissions and improves the early strength and durability of the material by adding early strength agents.

Benefits of technology

It has achieved efficient reuse of phosphogypsum and multi-source solid waste, reduced energy consumption and carbon emissions, improved the water stability and durability of materials, and reduced the mining of natural resources and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504188A_ABST
    Figure CN119504188A_ABST
Patent Text Reader

Abstract

The invention discloses lightweight aggregate based on ardealite and multi-source solid waste as well as a preparation method and a utilization method of the lightweight aggregate, and aims to solve the problems of low utilization rate of the ardealite and the multi-source solid waste, high energy consumption and high carbon emission of a utilization scheme, insufficient long-term water stability of a recycled product and the like in the prior art. The phosphogypsum and the multi-source solid waste are gelatinized by using the alkali activator, so that the solid waste generates viscosity to form a polymerized gel material, and the gelatinization process is realized by using the activity of the industrial solid waste, so that the lightweight aggregate with high strength and good performance is obtained. And meanwhile, the lightweight aggregate is classified in a cascade manner according to different strength grades of the lightweight aggregate, so that the practicability of the recycled product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a lightweight aggregate based on phosphogypsum and multi-source solid waste, and a preparation and utilization method thereof. Background Art

[0002] With the development of industrial production, the amount of industrial solid waste is increasing day by day, with various types and complex components, which makes it difficult to deal with. At present, only a limited number of industrial wastes are utilized, and other industrial solid wastes are still mainly stored. Some harmful industrial solid wastes are disposed of by landfill, incineration, chemical conversion and other methods. At present, the accumulation of phosphogypsum is large and its accumulation is increasing every year. The comprehensive utilization rate is less than 40%, and most of it can only be stored in large landfills and water bodies. Landfills cover a large area and occupy a large amount of land resources. There are safety hazards, and the toxic and harmful substances of phosphogypsum will accumulate in the surrounding soil or flow into the water, causing serious environmental pollution to the soil, water environment and atmosphere. Studies have found that the use of active silicon-aluminum industrial waste can generate an amorphous three-dimensional network structure composed of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons under alkaline excitation conditions. It is a green, environmentally friendly, and low-cost cementitious material. Compared with cement, it has excellent properties such as low carbon emissions, high temperature resistance and solidification of heavy metals.

[0003] At present, phosphogypsum can be used as roadbed filler and base filler after simple improvement. Although its mechanical strength meets the requirements of road filling, it has the problem of long-term water stability. A phosphogypsum lightweight aggregate prepared by mixing a certain proportion of phosphogypsum and slag with a sufficient amount of cement through rotating disc granulation has certain utilization methods, but its preparation process is complicated and consumes a lot of cement. In cement production, a clinker calcination step is required. The high temperature during the clinker calcination process not only consumes a lot of energy, but also produces a large amount of carbon dioxide (CO2) emissions, which is an important aspect of the cement industry's impact on the environment. Therefore, a more environmentally friendly and long-term water-stable phosphogypsum and multi-source solid waste recycling solution is needed. Summary of the invention

[0004] The purpose of the present invention is to provide a lightweight aggregate based on phosphogypsum and multi-source solid waste and a method for preparing and utilizing the same, so as to overcome the problems in the prior art of low utilization rate of phosphogypsum and multi-source solid waste, high energy consumption and high carbon emissions of the utilization scheme, and insufficient long-term water stability of the recycled products.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste comprises the following steps:

[0007] S1, taking phosphogypsum, fly ash and slag in proportion, mixing the fly ash with part of the phosphogypsum and slag to obtain a mixture A, and mixing the remaining phosphogypsum and slag to obtain a mixture B;

[0008] S2, mixing the base activator and the mixture A uniformly to obtain a gelled mixture;

[0009] S3, uniformly mixing the mixture B, the early strength agent and the gelled mixture to obtain a raw material mixture;

[0010] S4, pouring the raw material mixture into an extrusion granulator for granulation to obtain a lightweight aggregate molding material;

[0011] S5, curing the lightweight aggregate molding material to obtain lightweight aggregate.

[0012] Furthermore, the lightweight aggregate raw materials include 50-60 parts of phosphogypsum, 30-40 parts of blast furnace slag, and 10 parts of fly ash in terms of mass.

[0013] Furthermore, when adding the early strength agent, the early strength agent is added uniformly while stirring the mixture.

[0014] Further, mixing the lightweight aggregate raw materials comprises the following steps:

[0015] Mixing lightweight aggregate raw materials includes the following steps:

[0016] S101, weighing phosphogypsum, fly ash and slag in a certain proportion and mixing them to obtain a mixture A. In this step, all fly ash is used, and the mixing proportion of the mixture A is:

[0017] Phosphogypsum: fly ash = 4:3;

[0018] Slag: fly ash = 1:1;

[0019] S102, mixing the remaining phosphogypsum and slag to obtain a mixture B.

[0020] Further, the preparation of the base activator comprises the following steps:

[0021] S111, weigh a certain mass of Na2SiO3, NaOH and water, the amount of the alkali activator is 12%, the adjustment modulus of the alkali activator is 1.0-1.5, the mass of water is 18%-22% of the mass of all phosphogypsum, slag and fly ash, and the purpose of adding water is to make the solid waste-based cementitious material fluid and make the phosphogypsum moist during extrusion granulation. ;

[0022] S112, pour water into a heating vessel and heat it to 40°C;

[0023] S113, pouring Na2SiO3 particles into water 2-3 times, stirring until the solution changes from white to turbid;

[0024] S114, add NaOH into a container and stir for 10 minutes, and let it stand for 2 to 3 hours for aging to obtain an alkaline activator.

[0025] Furthermore, when the mixture A consisting of phosphogypsum, fly ash, slag and the alkali activator are poured into a stirring container for mixing, the mixture is first stirred at a low speed for 120 seconds, and then stirred at a high speed for 120 seconds after cleaning the residue on the blades.

[0026] Furthermore, a mixture B consisting of phosphogypsum, slag and an early strength agent is poured into a stirring container and mixed with the gelled mixture and stirred at a low speed for 180 seconds. The mass of the early strength agent is 0.5% to 1.0% of the mass of all phosphogypsum, slag and fly ash. The main component of the early strength agent is CaCl2. The purpose is to improve the early bonding strength of the phosphogypsum in the lightweight aggregate during extrusion granulation.

[0027] A lightweight aggregate based on phosphogypsum and multi-source solid waste, the lightweight aggregate is made by the above-mentioned preparation method. The lightweight aggregate raw materials include phosphogypsum, blast furnace slag, fly ash, early strength agent, water, Na2SiO3 and NaOH. The main components of the phosphogypsum are CaO and SO3; the proportion of SiO2 and Al2O3 in the fly ash exceeds 70%; the proportion of CaO and SiO2 in the slag is close to 70%.

[0028] Furthermore, the lightweight aggregate raw materials include 50-60 parts of phosphogypsum, 30-40 parts of blast furnace slag, and 10 parts of fly ash in terms of mass.

[0029] Furthermore, the particle size of the lightweight aggregate is 8 to 10 mm, the water absorption rate is 3% to 6% in 1 hour, and the bulk density is 900 to 1000 kg / m 3 , the cylinder pressure strength is 5~8MPa.

[0030] A method for utilizing lightweight aggregate based on phosphogypsum and multi-source solid waste, comprising the following steps:

[0031] S201, perform tests on lightweight aggregate and record the test results;

[0032] S202, taking 7 MPa in the cylinder pressure strength test result as the dividing point, classify the lightweight aggregates, and classify the lightweight aggregates with a test result of 5 to 7 MPa as low-grade products, and classify the lightweight aggregates with a test result greater than 7 MPa as high-grade products;

[0033] S203, the lightweight aggregate is utilized in different grades.

[0034] Compared with the prior art, the present invention has the following beneficial technical effects:

[0035] The present invention provides a method for preparing a lightweight aggregate based on phosphogypsum and multi-source solid waste. By using an alkali activator to gel the phosphogypsum and multi-source solid waste, the solid waste itself generates viscosity to form a geogel polymer material. The properties of industrial solid waste itself are used to achieve the gelling process, and the cement required in the traditional phosphogypsum recycling scheme is no longer used, thus avoiding the energy consumption and carbon dioxide (CO2) emissions caused by the clinker calcination step in cement production. Furthermore, the preparation method of the present invention adds an early strength agent and an alkali activator, so that the gelling product produced in the preparation process can effectively wrap and cement the undissolved phosphogypsum and admixtures, ensuring the water stability of the material, while improving the early strength and durability of the lightweight aggregate while improving the polymerization degree of the system, highlighting the characteristics of "early strength and fast setting", which can shorten the construction period and improve the construction efficiency.

[0036] The present invention provides a lightweight aggregate based on phosphogypsum and multi-source solid waste, which uses phosphogypsum and multi-source solid waste as raw materials, wherein the multi-source solid waste includes blast furnace slag and fly ash, thereby increasing the utilization ratio of industrial solid waste and reducing the storage of industrial solid waste and the pollution to the environment. At the same time, the lightweight aggregate described in the present invention uses industrial waste to replace natural aggregates, reduces the exploitation of natural resources, reduces the cost of use, reduces damage to the environment, and realizes the recycling of resources. Furthermore, the lightweight aggregate described in the present invention has higher strength, a denser structure, and good impermeability and frost resistance. The advantages of light weight, high strength, fire resistance, and high temperature resistance enable it to be used in combination with natural aggregates as a road base, and can also be used as a geopolymer concrete aggregate to cast non-structural concrete components.

[0037] The present invention provides a method for utilizing lightweight aggregate based on phosphogypsum and multi-source solid waste. The method adopts a tiered utilization strategy to classify lightweight aggregate in tiers according to different strength grades of lightweight aggregate, thereby improving the practicality of the recycled product, overcoming the previous single utilization mode of various solid wastes such as phosphogypsum, forming a multi-source solid waste composite utilization system, greatly reducing the dumping of solid wastes such as phosphogypsum, alleviating their pollution to the environment, and broadening their utilization channels. The method has large-scale promotion value and promotes the high-value utilization of solid wastes such as phosphogypsum. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The present invention is a schematic flow chart of a method for preparing a lightweight aggregate based on phosphogypsum and multi-source solid waste in an embodiment of the present invention.

[0039] Figure 2 The present invention is a schematic diagram of the preparation process of mixed lightweight aggregate raw materials in a method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste in an embodiment of the present invention.

[0040] Figure 3 The present invention is a schematic diagram of the preparation process of an alkali activator in a method for preparing a lightweight aggregate based on phosphogypsum and multi-source solid waste in an embodiment of the present invention.

[0041] Figure 4 The present invention is a schematic flow chart of a method for utilizing lightweight aggregate based on phosphogypsum and multi-source solid waste in an embodiment of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0044] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "provided with", "set / connected", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0045] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "several" is two or more, unless otherwise clearly and specifically defined.

[0046] Embodiment 1:

[0047] This embodiment provides a method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste, such as Figure 1 As shown, the preparation method comprises the following steps:

[0048] S1, taking phosphogypsum, fly ash and slag in proportion, mixing the fly ash with part of the phosphogypsum and slag to obtain a mixture A, and mixing the remaining phosphogypsum and slag to obtain a mixture B;

[0049] S2, mixing the base activator and the mixture A uniformly to obtain a gelled mixture;

[0050] S3, uniformly mixing the mixture B, the early strength agent and the gelled mixture to obtain a raw material mixture;

[0051] S4, pouring the raw material mixture into an extrusion granulator for granulation to obtain a lightweight aggregate molding material;

[0052] S5, curing the lightweight aggregate molding material to obtain lightweight aggregate.

[0053] Preferably, the lightweight aggregate raw material in this embodiment includes 50 parts of phosphogypsum, 40 parts of slag, and 10 parts of fly ash by weight. Based on a total weight of 1000g, there are 500g of phosphogypsum, 400g of slag, and 100g of fly ash.

[0054] Preferably, Figure 2 As shown, in this embodiment, mixing lightweight aggregate raw materials includes the following steps:

[0055] S101, weighing phosphogypsum, fly ash and slag in a certain proportion and mixing them to obtain a mixture A. In this step, all fly ash is used, and the mixing proportion of the mixture A is:

[0056] Phosphogypsum: fly ash = 4:3;

[0057] Slag: fly ash = 1:1;

[0058] S102, mixing the remaining phosphogypsum and slag to obtain a mixture B.

[0059] Preferably, in this embodiment, based on the mass of fly ash, 130g of phosphogypsum, 100g of fly ash and 100g of slag are taken out respectively according to the ratio of phosphogypsum: fly ash = 4:3 and slag: fly ash = 1:1, and they are mixed evenly, and the remaining 370g of phosphogypsum and 300g of slag are mixed evenly.

[0060] Preferably, Figure 3 As shown, the preparation of the base activator in this embodiment includes the following steps:

[0061] S111, weighing a certain mass of Na2SiO3, NaOH and water, wherein the amount of the alkali activator is 12%, the adjustment modulus of the alkali activator is 1.0-1.5, and the mass of water is 18%-22% of the mass of all phosphogypsum, slag and fly ash;

[0062] S112, heating water to 40°C;

[0063] S113, pouring Na2SiO3 particles into water 2-3 times, stirring until the solution changes from white to turbid;

[0064] S114, add NaOH into a container and stir for 10 minutes, and let it stand for 2 to 3 hours for aging to obtain an alkaline activator.

[0065] Preferably, when preparing the alkaline activator in this embodiment, 30 g of Na2SiO3 solid powder and 11.4 g of NaOH flake solid are weighed.

[0066] Preferably, in this embodiment, when a mixture A consisting of phosphogypsum, fly ash, and slag and an alkali activator are poured into a stirring container for mixing, the mixture is first stirred at a low speed for 120 seconds, and after cleaning the residue on the blades, the mixture is stirred at a high speed for another 120 seconds.

[0067] Preferably, in this embodiment, a mixture B consisting of phosphogypsum, slag and an early strength agent is poured into a stirring container and mixed with the gelled mixture and stirred at a low speed for 180 seconds. The amount of the early strength agent added is 1.0% of the total mass of the phosphogypsum, slag and fly ash. In this embodiment, 10 g of the early strength agent is added.

[0068] Preferably, a method for preparing a lightweight aggregate based on phosphogypsum and multi-source solid waste in this embodiment is as follows:

[0069] Weigh 200 g of water, 30 g of Na2SiO3 and 11.4 g of NaOH solid particles required for the test, and heat the weighed water to 40°C on a magnetic stirrer;

[0070] Pour Na2SiO3 particles into water twice, stir until the solution changes from white to turbid, then add NaOH. Stir at a low speed of 150r / min for 10min, and let it stand for 2h for aging before use;

[0071] Weigh 500 g, 100 g, and 400 g of phosphogypsum, fly ash, and slag for preparing lightweight aggregate according to their mass fractions, respectively; based on the mass of fly ash, take out 130 g of phosphogypsum, 100 g of fly ash, and 100 g of slag according to the ratio of phosphogypsum: fly ash = 4:3, and slag: fly ash = 1:1, and mix them evenly to obtain a mixture A; mix the remaining 370 g of phosphogypsum and 300 g of slag evenly to obtain a mixture B;

[0072] Pour 130g of phosphogypsum, 100g of fly ash, 100g of slag mixture A and the prepared alkali activator into a mortar mixing pot, stir at a low speed of 150r / min for 120s, scrape the residue on the blade with a scraper, and then stir at a high speed of 300r / min for 120s;

[0073] Pour the remaining 370g of phosphogypsum and 300g of slag mixture B into a stirring pot, weigh 10g of early strength agent and add it, and stir at a low speed of 150r / min for 180s;

[0074] Pour the stirred mixture into the extrusion granulator and start granulation;

[0075] The granulated material was cured for 28 days under a standard environment of temperature 20° C. and humidity 95% to obtain lightweight aggregate.

[0076] Embodiment 2:

[0077] This embodiment provides another method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste, wherein the overall preparation steps are substantially the same as the preparation steps described in Example 1, except that the lightweight aggregate raw materials in this embodiment are prepared as follows:

[0078] According to the mass fraction, take 60 parts of phosphogypsum, 30 parts of slag, and 10 parts of fly ash. According to the total mass of 1000g and the water content of 0.20, that is, 600g of phosphogypsum, 300g of slag, 100g of fly ash, and 200g of water. Among them, based on the mass of fly ash, take out 130g of phosphogypsum, 100g of fly ash, and 100g of slag respectively according to the ratio of phosphogypsum: fly ash = 4:3, slag: fly ash = 1:1, and mix them evenly. Mix the remaining 470g of phosphogypsum and 200g of slag evenly, and weigh 30g of Na2SiO3 solid powder and 11.4g of NaOH flake solid.

[0079] Embodiment 3:

[0080] In this embodiment, a lightweight aggregate based on phosphogypsum and multi-source solid waste is provided. The lightweight aggregate is made of phosphogypsum, blast furnace slag, fly ash, early strength agent, water, Na2SiO3 and NaOH.

[0081] The lightweight aggregate raw materials include 50 parts of phosphogypsum, 40 parts of blast furnace slag and 10 parts of fly ash in terms of mass.

[0082] The particle size of the lightweight aggregate is 8-10 mm, the water absorption rate is 3%-6% in 1 hour, and the bulk density is 900-1000 kg / m 3 , the cylinder pressure strength is 5~8MPa.

[0083] Among them, the sources and main components of the phosphogypsum and multi-source solid waste of the lightweight aggregate described in this embodiment are as follows:

[0084] Phosphogypsum: It is an industrial by-product discarded from the production of phosphate fertilizers. It is in powder form and its main components are CaO and SO3, and it contains some heavy metal ions.

[0085] Fly ash: It comes from thermal power plants and becomes powder after processing. Its main components are SiO2 and Al2O3. It contains Si and Al active substances and is often used with cement to improve later strength.

[0086] Slag: It comes from steel mills and is in powder form after processing. Its main components are CaO and SiO2. Adding an appropriate amount of slag can enhance the performance of concrete. The slag used in the present invention is S105 (a grade description of slag powder, which refers to slag powder with higher activity and finer particle size).

[0087] Alkali activator: Alkali metal silicates have more stable activating properties than other alkaline salts, but the modulus requirement is 1.0 to 1.5. The solid instant Na2SiO3 used in the present invention has a modulus of 3, and NaOH needs to be added to adjust the modulus to 1.4.

[0088] Preferably, the lightweight aggregate based on phosphogypsum and multi-source solid waste described in this embodiment is extruded, and the active silicon-aluminum substances in fly ash and slag react with Ca in slag and phosphogypsum under the action of alkali. 2+ The reaction produces dense calcium silicate hydrate and calcium aluminosilicate hydrate, which provide certain gelling properties, allowing the powdered multi-source solid waste to quickly agglomerate and develop strength after a certain curing time.

[0089] Embodiment 4:

[0090] This embodiment provides another lightweight aggregate based on phosphogypsum and multi-source solid waste, and its overall structure is basically the same as the overall structure of the lightweight aggregate based on phosphogypsum and multi-source solid waste described in Example 3, except that the lightweight aggregate raw materials described in this embodiment are calculated by weight as follows:

[0091] 60 parts of phosphogypsum, 30 parts of slag, and 10 parts of fly ash.

[0092] Embodiment 5:

[0093] This embodiment provides a method for utilizing lightweight aggregate based on phosphogypsum and multi-source solid waste, comprising the following steps:

[0094] S201, perform tests on lightweight aggregate and record the test results;

[0095] S202, taking 7 MPa in the cylinder pressure strength test result as the dividing point, classify the lightweight aggregates, and classify the lightweight aggregates with a test result of 5 to 7 MPa as low-grade products, and classify the lightweight aggregates with a test result greater than 7 MPa as high-grade products;

[0096] S203, the lightweight aggregate is utilized in different grades.

[0097] Among them, the test on lightweight aggregate is to measure the bulk density, cylinder pressure strength and water absorption of lightweight aggregate in accordance with "Lightweight Aggregate and Its Test Methods" (GB / T 17431-2010).

[0098] In this example, the lightweight aggregate prepared in Example 1 was selected for testing.

[0099] The bulk density test process is as follows:

[0100] The lightweight aggregate is screened using a sieve with a mesh size of 4.75 mm, with the particle size of 4.75 mm being the boundary. The lightweight aggregate with a particle size of less than or equal to 4.75 mm passing through the mesh is the fine aggregate, and the lightweight aggregate with a particle size greater than 4.75 mm remaining on the sieve is the coarse aggregate. The bulk density test should be carried out with 30L to 40L of coarse aggregate or 15L to 20L of fine aggregate. In this embodiment, 30L of coarse aggregate is preferably used for the test.

[0101] Take 30L of coarse aggregate and put it into a drying oven. After drying to a constant weight, divide it into two parts for later use;

[0102] Prepare a volumetric cylinder, take a portion of the coarse aggregate, and pour the sample evenly into the container from 50 mm above the container mouth using a sampling spoon or shovel (or use a standard funnel), allowing the sample to fall naturally without hitting the volumetric cylinder to simulate the natural accumulation state;

[0103] After filling, make the sample on the top of the volume cylinder pile up into a cone, then use a ruler to scrape it from the center to both sides along the edge of the volume cylinder, fill the concave surface with aggregates with smaller particle size, weigh and record the total mass of the sample and the volume cylinder, and calculate the bulk density (ρ) based on the sample mass (m) and the volume (V) of the volume cylinder. The formula is:

[0104]

[0105] A second test was performed using another sample and the average result was taken as the final result.

[0106] The water absorption test process is as follows:

[0107] Take 4L lightweight aggregate as a sample, sieve it with a sieve with a mesh size of 2.36mm, and dry the residue to a constant weight;

[0108] Mix the dried sample evenly, divide it into three equal parts, weigh them respectively and record them as m 干 ;

[0109] Place the sample in a water container and immerse it in water. If there are particles floating on the water, press them into the water to ensure that the sample is completely covered by water.

[0110] After the sample is immersed in water for 1 hour or 24 hours, it is taken out. In this embodiment, it is preferred to take out the sample after immersion in water for 1 hour, pour it into a 2.36 mm sieve to filter the water for 1 minute, and then pour it on a wrung wet towel. Hold the two ends of the towel with your hands to make it into a groove shape, and let the sample roll back and forth on the towel until the excess water on its surface is completely removed. Then pour the sample into an enamel dish, weigh it, and record it as m 湿 .

[0111] According to the mass of the dry sample m 干 and sample wet weight m 湿 Calculate the water absorption rate A, the formula is:

[0112]

[0113] The water absorption rate of the other two samples was tested again according to the above steps, and the average value was taken as the final result.

[0114] The cylinder pressure strength test process is as follows:

[0115] Use a sieve with a mesh size of 10 mm to sift 5 L of lightweight aggregate with a nominal particle size of 10 mm to 20 mm as a sample;

[0116] According to the requirements of bulk density loading, use a pressure cylinder with a cylinder bottom to load the sample to the top of the cylinder mouth, place it on the concrete test vibration table and vibrate for 3s, then load the sample to the top of the cylinder mouth, place it on the vibration table and vibrate for 5s. Scrape (or fill) the sample to the top of the cylinder mouth;

[0117] Install the guide cylinder and the punching die, aligning the lower scale line of the punching die with the upper edge of the guide cylinder;

[0118] Place the pressure cylinder on the lower platen of the press, align it with the center of the platen, and apply load at a uniform speed of 300N to 500N per second. When the punching die is pressed to a depth of 20mm, record the pressure value.

[0119] The final measured bulk density of the lightweight aggregate prepared in Example 1 is 936.27 kg / m 3 , water absorption is 5.22%, and cylinder pressure strength is 7.16MPa. According to the measured bulk density, the density grade is divided into 900 in accordance with "Light Aggregate and Its Test Methods" (GB / T17431-2010). At this density grade, the 1h water absorption of lightweight aggregate is required to be less than 10%, and the cylinder pressure strength is greater than 5MPa, thus meeting the specification requirements.

[0120] According to the cylinder compressive strength that meets the specifications, the lightweight aggregate of phosphogypsum and multi-source solid waste for road engineering is classified as a low-grade product with a strength of 5-7MPa, and a high-grade product with a strength greater than 7MPa. The lightweight aggregate in this embodiment is a high-grade product, which is recommended for use in non-structural concrete such as road base and curbstones, and has good water stability and durability.

[0121] Embodiment 6:

[0122] This embodiment provides another method for utilizing lightweight aggregate based on phosphogypsum and multi-source solid waste. The utilization method described in this embodiment is roughly the same as that described in Example 5, with the difference that the experimental samples used in this embodiment are taken from the lightweight aggregate prepared in Example 2.

[0123] The same test steps as in Example 5 were used to measure the bulk density of the lightweight aggregate prepared in Example 2 to be 925.18 kg / m 3 , water absorption is 3.15%, and cylinder pressure strength is 6.28MPa. According to the measured bulk density, the density grade is divided into 900 in accordance with "Light Aggregate and Its Test Methods" (GB / T 17431-2010). Under this density grade, the 1h water absorption of lightweight aggregate is required to be less than 10%, and the cylinder pressure strength is greater than 5MPa, thus meeting the requirements of the specification.

[0124] According to the cylinder pressure strength that meets the specifications, the lightweight aggregate of phosphogypsum and multi-source solid waste for road engineering is classified as a low-grade product with a strength of 5-7MPa, and a high-grade product with a strength greater than 7MPa. The lightweight aggregate in this embodiment belongs to a low-grade product, and is recommended for use in road cushions and other parts with low requirements for driving bearing capacity. It has good frost resistance and ensures that the base layer is not harmed by frost heave and slurry boiling.

[0125] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste, characterized in that: The following steps are involved: S1, taking phosphogypsum, fly ash and slag in proportion, mixing the fly ash with part of the phosphogypsum and slag to obtain a mixture A, and mixing the remaining phosphogypsum and slag to obtain a mixture B; S2, mixing the base activator and the mixture A uniformly to obtain a gelled mixture; S3, uniformly mixing the mixture B, the early strength agent and the gelled mixture to obtain a raw material mixture; S4, pouring the raw material mixture into an extrusion granulator for granulation to obtain a lightweight aggregate molding material; S5, curing the lightweight aggregate molding material to obtain lightweight aggregate.

2. The method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste according to claim 1, characterized in that: The lightweight aggregate raw materials include 50-60 parts of phosphogypsum, 30-40 parts of blast furnace slag and 10 parts of fly ash in terms of weight.

3. The method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste according to claim 2, characterized in that: Mixing lightweight aggregate raw materials includes the following steps: S101, weighing phosphogypsum, fly ash and slag in a certain proportion and mixing them to obtain a mixture A. In this step, all fly ash is used, and the mixing proportion of the mixture A is: Phosphogypsum: fly ash = 4:3; Slag: fly ash = 1:1; S102, mixing the remaining phosphogypsum and slag to obtain a mixture B.

4. The method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste according to claim 1, characterized in that: The preparation of the base activator comprises the following steps: S111, weighing a certain mass of Na2SiO3, NaOH and water, wherein the amount of the alkali activator is 12%, the adjustment modulus of the alkali activator is 1.0-1.5, and the mass of water is 18%-22% of the mass of all phosphogypsum, slag and fly ash; S112, heating water to 40°C; S113, pouring Na2SiO3 particles into water 2-3 times, stirring until the solution changes from white to turbid; S114, add NaOH into a container and stir for 10 minutes, and let it stand for 2 to 3 hours for aging to obtain an alkaline activator.

5. The method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste according to claim 1, characterized in that: When the mixture A consisting of phosphogypsum, fly ash and slag is mixed with the alkali activator, it is stirred at a low speed for 120 seconds, and then the residue on the blades is cleaned and stirred at a high speed for 120 seconds.

6. The method for preparing lightweight aggregate based on phosphogypsum and multi-source solid waste according to claim 1, characterized in that: When the mixture B consisting of phosphogypsum and slag and the early strength agent are mixed with the gelled mixture, they are stirred at a low speed for 180 seconds, wherein the mass of the early strength agent is 0.5% to 1.0% of the mass of all the phosphogypsum, slag and fly ash.

7. A lightweight aggregate based on phosphogypsum and multi-source solid waste, characterized in that: The lightweight aggregate is made of phosphogypsum, blast furnace slag, fly ash, early strength agent, water, Na2SiO3 and NaOH.

8. The lightweight aggregate based on phosphogypsum and multi-source solid waste according to claim 7, characterized in that: The lightweight aggregate raw materials include 50-60 parts of phosphogypsum, 30-40 parts of blast furnace slag and 10 parts of fly ash in terms of weight.

9. The lightweight aggregate based on phosphogypsum and multi-source solid waste according to claim 7, characterized in that: The particle size of the lightweight aggregate is 8-10 mm, the water absorption rate is 3%-6% in 1 hour, and the bulk density is 900-1000 kg / m 3 , the cylinder pressure strength is 5~8MPa.

10. A method for utilizing lightweight aggregate based on phosphogypsum and multi-source solid waste, characterized in that: The following steps are involved: S201, perform tests on lightweight aggregate and record the test results; S202, taking 7 MPa in the cylinder pressure strength test result as the dividing point, classify the lightweight aggregates, and classify the lightweight aggregates with a test result of 5 to 7 MPa as low-grade products, and classify the lightweight aggregates with a test result greater than 7 MPa as high-grade products; S203, the lightweight aggregate is utilized in different grades.

Citation Information

Cited By

  • High-strength environment-friendly ardealite nano geopolymer aggregate and preparation method thereof

    CN121135253A